2015
DOI: 10.1007/s10643-015-0750-1
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Talk, But a “Dance”! How Kindergarten Teachers Opened and Closed Spaces for Teacher–Child Authentic Dialogue

Abstract: Although authentic dialogue between teachers and young children is vital to the learning process, increasingly diverse student populations and a focus on high-stakes testing, challenge teachers' approaches to such conversations. This study examined the verbal and nonverbal interactions between five teachers and young children using child-taken photographs to promote conversation. Analysis exposed how the teachers' nonverbal and verbal responsiveness opened and closed conversational spaces for the children to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…The analysis revealed that as teachers provided open conversational spaces with children, authentic dialogue emerged. Both voices were expressed in a more equalitative fashion and the child's world was heard (Strickland & Marinak, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that as teachers provided open conversational spaces with children, authentic dialogue emerged. Both voices were expressed in a more equalitative fashion and the child's world was heard (Strickland & Marinak, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…When a teacher withholds the urge to control the child's thinking or reprimand their behaviour, she can actively listen and be attentive to the children's needs. Respectful and responsive interactions that also honor cultural beliefs and values will strengthen the teacher's relationships with the children and their families (Barrera, Corso & MacPherson, 2003;Strickland & Marinak, 2015). Nystrand and his colleagues defined this space as a "positive interaction area" in which many children participate, build on each other's ideas and ask questions enthusiastically and out of interest (Nystrand et al, 2003).…”
Section: The Role Of Dialogue In Educationmentioning
confidence: 99%
“…As Alexander (2008) argues, partners involved in dialogue see each other's as equals, and are in constant desire to attain insights into each other's inner personal thoughts, this in turn creates interpersonal relationships. A deeper form of dialogue, termed authentic dialogue, is defined as the creation of open and honest spaces in which diverse perspectives are valued and ambiguity is accepted and not rejected (Strickland & Marinak, 2015). Within the authentic dialogue space, multiple voices are encouraged in order to enable personal stories to be heard.…”
Section: Ground Theories Of Dialogical Approachmentioning
confidence: 99%
“…The teacher dominates the discourse and children's voices are only heard when they need to respond to the questions at hand, leaving them no space to actively participate in the dialogue (Mehan & Cazden, 2015). Strickland and Marinak (2015) explain that when the teachers voice is heard throughout most of the dialogue and the child's voice is constrained, spaces are closed and prove uninviting for children's participation. Hence, the way teachers view the use of classroom dialogue will either support or interfere with the way children learn (Mercer, 2019).…”
Section: Authentic Dialogue In Educationmentioning
confidence: 99%
See 1 more Smart Citation